(3GdbGfhfs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3hHYO abO GdJeS efi HYV NdU ENhGfi , ef HdRefi ESYGaI Cf CUfa ai GdWH cJGHkG eTJedkG Ydi bhGfjfg GdcdjI hGdLRFjI CTJeGdkG jLeY Edi GdTQM s
(3BNQgG (B:s
(3RjLjH Cf JSJYed GdeNQLGJ HYO GdGSJaQGZ MJi JfbWY GdeGOI GdefUHI Edi Pdc GdYVh hCjVkG LejY eG jfaN GdChQGe hjaLQgG , hGdeNOQGJ CbhGgG GdCajhf , hef LedJgG GdfaGN s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GfXQgG eY bGfhfLI ddLaejfi Qbe (B" 637-641"s
(3JTJed Ydi GdcJGH GdChd ai GdCehQ GdcdjI ai GdWHs
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B176 s
Keywords: (3GdWHs